The Reuse of Circular External Fixator Components: An Assessment of Safety and Potential Savings - Chironga, Kudzai (Division of General Surgery, 2023)
Purpose: Cost saving strategies are important especially in a resource constrained environment. One such strategy well supported in literature is the reuse of temporary monolateral external fixator components, a strategy we utilize at our institution. The aim of the study was to determine the safety and cost saving associated with the reuse of definitive circular external fixator components in a resource constrained environment. Method: We performed a retrospective review of all adult patients who were treated with either new or reused circular external fixators from a single manufacturer between January and December 2017. Reused circular external fixator components, excluding half pins and wires, were subjected to an in-house reprocessing protocol. Cost savings were calculated as the difference between the price of a completely new frame and the amount invoiced for new components only in a reused frame. Results: 33 patients were included in the study with an average age of 31.9 years. The mean duration of treatment with a circular external fixator was 5.8 months. No mechanical failure events were recorded during the study period. Our institution saved approximately 52% (R717 503.89) and 63 % (R136 568.19) of expected total cost for hexapod and Ilizarov frames respectively. Conclusion: The strategy of reusing circular external fixator components is unconventional and this study was conducted to evaluate the safety and potential savings in a resource constrained environment. We demonstrated this practice to be reasonably safe and to result in significant cost savings which might be relevant in low-and-middle income countries (LMICs).